Knowing nursing team care practices in relation to newborns in end-of-life situations - Isabella Navarro Silva; Natália Rejane Salim; Regina Szylit; Patricia Stella Silva Sampaio; Carolliny Rossi de Faria Ichikawa; Maiara Rodrigues dos Santos (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: Understand the care practices experiences of nursing staff in relation to providing end-of-life care to newborns and their families in neonatal intensive care units (NICU). Method: Descriptive study with a qualitative approach, involving eight nursing professionals from an NICU. Results: Through the data analysis, it was possible to identify three central themes: the "obscurity of death in neonatal ICUs": coping with death at the onset of a human life; palliative care and end-of-life decisions: the challenges faced by nursing staff in neonatal ICUs; and types of nursing care in the daily activities of neonatal ICUs. Conclusion: It is essential to understand the experiences and needs of nursing staff, so that proposals can be formulated for seeking improvements in the care relationships that take place in this context.